RURAL LIVELIHOODS DIVERSITY: COPING STRATEGIES IN WA WEST DISTRICT IN NORTHERN GHANA - Aasoglenang, Arkum Thaddues; Bonye, Samuel Z. (European Scientific Journal, ESJ, 2013)
It is evidence that for several years rural communities in Northern Ghana have been confronted with single rainfall season which is also unpredictable. The poor weather condition has cumulatively contributed to the high incidence of poverty among households. In the midst of this, the indigenes have stayed and persevered through other diversified means of survival with little or no external support. The study therefore seeks to identify traditional and diversified livelihoods coping mechanisms that these rural families have adopted to at least secure them, minimal food and other socio-economic security/assets. Participatory Rapid Appraisal (PRA) techniques were mostly used to collect data. Some of the techniques used were group discussions, wealth ranking, structured and unstructured questionnaires, and observation. The data analysis employed both qualitative and quantitative approaches to examine the key issues identified. The study reveals that, most communities are living in difficult condition but are resilient to make ends meet. They have done this through diversification of their livelihood portfolios which include diversified crop cultivation, livestock rearing, dry season gardening, petty trading and especially outmigrant remittances. This strategy adopted also enable them cope with other competing demands in terms of food, healthcare, education, farming and shelter among others. The study observed that farmers/households will do better if they are incentivized (inputs and extension service) to boost subsistence farming, diversify more into income generating activities (animal rearing).